Pengaruh Kualitas Pelayanan dan Pengalaman Pelanggan Terhadap Loyalitas Pelanggan pada Konsumen Wizzmie Tlogomas Malang - Marienella Dyva Saskya; Ayu Sulasari; Joko Samboro (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Service quality and customer experience are important factors influencing customer loyalty in the food industry, including at the Wizzmie Tlogomas Malang restaurant. Based on observations, there was a discrepancy between positive customer reviews on Google Maps and the actual service conditions on-site, such as dirty plates on empty tables and inconsistent service. This study aims to analyze the influence of service quality and customer experience on customer loyalty at Wizzmie Tlogomas Malang, both partially and simultaneously. This study uses a quantitative approach with an explanatory research design. The variables studied include service quality, customer experience, and customer loyalty. Data were collected through observation, questionnaires, and interviews. Using purposive sampling, 100 respondents were selected from consumers who had made at least two purchases at Wizzmie Tlogomas. Data were analyzed using validity and reliability tests, multiple linear regression, and t-tests and F-tests with the assistance of SPSS software. The results showed that service quality has a positive and significant effect on customer loyalty. In addition, customer experience also has a positive and significant effect on customer loyalty. Overall, service quality and customer experience have a positive and significant effect on customer loyalty. From the results of this study, it can be concluded that service quality and customer experience influence customer loyalty, so Wizzmie Tlogomas Malang needs to maintain consistent service and create positive experiences to keep customers loyal.